Pengembangan Biopot Berbasis Limbah Peternakan Dan Pertanian Di Desa Sukadana, Kecamatan Pujut, Kabupaten Lombok Tengah: Solusi Ramah Lingkungan Untuk Pengelolaan Limbah - Wahyuningsih, Endah; Firmansyah, M. Arief; Julianto, Meutia Sri; Putri, Ni Wayan Suci Anjani; Zulkarnaen, Niken; Rastuti, Hesti Fuji (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The Community Empowerment Program (KKN PMD) of Universitas Mataram for the 2024 period is an implementation of the university's tri-dharma mission, carried out in an interdisciplinary and institutional manner with the theme of Green Economy, Advanced and Sustainable Agriculture. This program aims to empower the community of Sukadana Village in Pujut District, Central Lombok, by actively utilizing cow dung waste and reducing the use of plastic polybags in agriculture. In practice, KKN PMD participants collaborate with the local community and village government to identify existing potentials and issues, and plan the production of biopots from cow dung as a solution. The results of this activity include enhanced knowledge and skills of the community in processing livestock waste into beneficial products, such as biopots, which help reduce waste accumulation and plastic use. This program also introduces environmentally friendly agricultural methods, expected to improve agricultural productivity. Overall, the KKN PMD program in Sukadana Village successfully empowered the community and supported sustainable agriculture through the utilization of livestock waste.